2013
DOI: 10.1080/08897077.2013.776658
|View full text |Cite
|
Sign up to set email alerts
|

Teaching and Assessing Residents’ Skills in Managing Heroin Addiction with Objective Structured Clinical Examinations (OSCEs)

Abstract: Background Heroin abusing patients present a significant challenge. Objective Structured Clinical Exams (OSCEs) allow evaluation of residents’ clinical skills. The objective of our study was to examine resident OSCE performance assessing and managing heroin abuse. Methods Evaluation and comparison of heroin-specific communication, assessment and management skills in a five-station PGY3 substance abuse OSCE. Faculty used a four-point Likert scale to assess residents’ skills; standardized patients provided wri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 25 publications
0
6
0
1
Order By: Relevance
“…We found that retention of the order of steps for naloxone administration when counseling patients on response to an overdose was increased among surveyed P2 students who received training from a didactic lecture plus an OSCE as compared with P1 student pharmacists who received a lecture only; however, overall fact-based knowledge related to naloxone and opioids was similar. We have retained both teaching components in our curriculum based on the strength of OSCE as a tool for teaching addiction, 46,47 the unremitting opioid epidemic in our state and region, and positive trends among surveyed P2 students related to an increased perception that overdose prevention with naloxone is not a waste of time or money.…”
Section: Discussionmentioning
confidence: 99%
“…We found that retention of the order of steps for naloxone administration when counseling patients on response to an overdose was increased among surveyed P2 students who received training from a didactic lecture plus an OSCE as compared with P1 student pharmacists who received a lecture only; however, overall fact-based knowledge related to naloxone and opioids was similar. We have retained both teaching components in our curriculum based on the strength of OSCE as a tool for teaching addiction, 46,47 the unremitting opioid epidemic in our state and region, and positive trends among surveyed P2 students related to an increased perception that overdose prevention with naloxone is not a waste of time or money.…”
Section: Discussionmentioning
confidence: 99%
“…20,23 Our program findings are similar to a program that used OSCEs to teach addiction management skills. 19,24 While this grant-funded program was highly regarded by both residents and residency program leadership, it was not sustained after grant support ended. Understanding the specific and unique challenges internal medicine residents face when implementing new safe opioid prescribing practices helps put our results in context.…”
Section: Discussionmentioning
confidence: 99%
“…8 Uma das formas de se avaliar as habilidades clínicas durante a simulação é por meio do exame clínico objetivo estruturado (OSCE), que é adequado para a avaliação da aprendizagem, principalmente nos domínios psicomotores e emocionais. 9 No OSCE, os participantes interagem com os pacientes padronizados em cenários realistas e realizam tarefas como entrevistas, exame físico e aconselhamento. 10 Atualmente, os simuladores de paciente podem ser classificados como de baixa fidelidade, estáticos, menos realísticos e usados para procedimentos específicos; de média fidelidade, mais realísticos e podem oferecer ausculta de sons respirató-rios, cardíacos, pulsação; e os de alta fidelidade, extremamente realísticos, com respostas em tempo real, identificados por meio de olhos funcionais, sons cardíacos, pulmonares, gastrintestinais e vocais, sangramentos e secreções.…”
Section: Introductionunclassified